Transnational democracy : political spaces and border crossings - Anderson, James, 1941- (London ; New York : Routledge, 2002)
A multidisciplinary array of experts explore the issues related to globalisation and democracy. They focus on federalism, multi-cultural societies, the European Union and potential agents for the democratisation of global institutions.
Questions of democracy, territoriality and globalisation / James Anderson -- Reconstituting the modern state / Bhikhu Parekh -- The limits of federalism in transnational democracy : beyond the hegemony of the US model / John Agnew -- Reconceptualising democracy in the European Union / Michael Newman -- Multi-level citizenship, identity and regions in contemporary Europe / Joe Painter -- Transnational integration and cross-border regions in the European Union / Liam O'Dowd -- Transnational democracy versus national conflict: border crossings in Ireland / James Anderson, Douglas Hamilton -- Democratising global institutions: possibilities, limits and normative foundations / Anthony McGrew -- Holding the middle ground in the transnationalisation process / Kees Van Der Pijl -- The democratic potential of non-governmental organisations / Joachim Hirsch -- Contesting corporate globalism : sources of power, channels for democratisation / James Goodman -- Relocating the demos? / Peter J. Taylor.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Democracy; World politics; Citizenship; Sovereignty; International organization; International relations; Politique mondiale; Souveraineté.; Organisation internationale; Relations internationales; sovereignty; international relations; POLITICAL SCIENCE -- Globalization; Citizenship; Democracy; International organization; International relations; Sovereignty; World politics